(untitled) (Plant Tissue Culture and Biotechnology, 2020)
The explants of two varities rosea and alba of Catharanthus roseus used for in vitro propagation and found to be more than 50% of the cultures became contaminated. The most common bacterial contaminants were Bacillus licheniformis, Micrococcus, Panibacillus and fungal contaminants were Fusarium, Alternaria, Cladosporium and Aspergillus. Combinations of different antibiotics (Penicillin, norfloxacin, tobramycin, gatifloxacin, ofloxacin) and fungicides (Bavastin, captan, fluconazole and trichoderma) were used to control the growth of the contaminants. Gatifloxacin and ofloxacin inhibited 100% growth of bacteria whereas, bavastin and captan appeared to be the most effective fungicides. Combination of gatifloxacin, ofloxacin with bavastin and captan inhibited the growth of contaminants at their minimum phytotoxic concentration (MIC). The observed minimum phytotoxic concentration (MPC) of ofloxacin, gatifloxacin, bavastin and captan was 15, 9, 6 and 5% at their respective MIC. More than 90% of the cultures responded for callus formation in the combination of gatifloxacin (4%) + bavastin (1%). While the combination of gatifloxacin and captan was highly toxic that reduces the growth of the culture. Plant Tissue Cult. & Biotech. 30(2): 297-305, 2020 (December)